AN ANALYSIS OF SUBSCIOUS THEME MOTIVE IN SAMUEL COLERIDGE POEM - Ghosh, Gargi; Saraswat, Varsha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the realm of supernaturalism and the subconscious mind, the poems "The Ancient Mariner" and "Kubla Khan" by Samuel Taylor Coleridge are considered to be the most significant works of literature. Coleridge was a poet who wrote about the occult and the subconscious, and he avoided everything that may be considered crass in his writings. The objective of this study, is to look for supernaturalism and subconscious theme in the key poems written by Samuel Taylor Coleridge. It is possible to refer to content analysis as "documentary activity" or "information analysis" due to the fact that it is concerned with the subject matter. Because they are not the product of an experiment, the data from this study are considered to be of the qualitative kind. They belong to the category of non-manipulated variables of this study. According to Gay (1987: 189), "descriptive research determines and reports the way the things are." This paper will demonstrate the nature of the situation with regard to how it was at the time of the study. The aspects of the supernaturalism and subconscious theme that are given in these poems include dream, suggestiveness, and vision.